Exercise-induced angiogenesis is attenuated by captopril but maintained under perindopril treatment in hypertensive rats - Macedo, Anderson G.; Miotto, Danyelle S.; Tardelli, Lidieli P.; Santos, Carlos F.; Amaral, Sandra L. (Frontiers in Physiology, 2023)
Angiogenesis is an important exercise-induced response to improve blood flow and decrease vascular resistance in spontaneously hypertensive rats (SHR), but some antihypertensive drugs attenuate this effect. This study compared the effects of captopril and perindopril on exercise-induced cardiac and skeletal muscle angiogenesis. Forty-eight Wistar rats and 48 SHR underwent 60 days of aerobic training or were kept sedentary. During the last 45 days, rats were treated with captopril, perindopril or water (Control). Blood pressure (BP) measurements were taken and histological samples from the tibialis anterior (TA) and left ventricle (LV) muscles were analyzed for capillary density (CD) and vascular endothelial growth factor (VEGF), VEGF receptor-2 (VEGFR-2) and endothelial nitric oxide synthase (eNOS) protein level. Exercise increased vessel density in Wistar rats due to higher VEGFR-2 (+17%) and eNOS (+31%) protein level. Captopril and perindopril attenuated exercise-induced angiogenesis in Wistar rats, but the attenuation was small in the perindopril group, and this response was mediated by higher eNOS levels in the Per group compared to the Cap group. Exercise increased myocardial CD in Wistar rats in all groups and treatment did not attenuate it. Both exercise and pharmacological treatment reduced BP of SHR similarly. Rarefaction was found in TA of SHR compared to Wistar, due to lower levels of VEGF (-26%) and eNOS (-27%) and treatment did not avoid this response. Exercise prevented these reductions in control SHR. While rats treated with perindopril showed angiogenesis in the TA muscle after training, those rats treated with captopril showed attenuated angiogenesis (-18%). This response was also mediated by lower eNOS levels in Cap group compared with Per and control group. Myocardial CD was reduced in all sedentary hypertensive compared with Wistar and training restored the number of vessels compared with sedentary SHR. In conclusion, taken into account only the aspect of vessel growth, since both pharmacological treatments reduced BP in SHR, the result of the present study suggests that perindopril could be a drug of choice over captopril for hypertensive practitioners of aerobic physical exercises, especially considering that it does not attenuate angiogenesis induced by aerobic physical training in skeletal and cardiac muscles.